The implementation of shari'ah compliance in Islamic banking : the role of the shari'ah board comparative study between (Malaysia and Indonesia) - Triyanta, Agus (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2009)
This study examines the implementation of shari'ah compliance in Islamic banking by comparing between two countries, Malaysia and Indonesia. This study seeks to answer whether or not along the rapid growth and development of Islamic banking, the issues on shari'ah compliance take place. Another question is whether the legal and regulatory frameworks are sufficiently provided pertinent to shari'ah compliance in Islamic banking. Lastly, the question on what is the role of the shari'ah board members in ensuring shari'ah compliance in Islamic banking is also in need for an answer. This research is a combination of library (documentary) research and field research. Statutory provisions, guidelines and other legal instruments are explored and analysed to understand the development of the Islamic banking business and whether the legal framework is adequate to cater to shari'ah compliance in Islamic banking. The field research is made in revealing the practical process in assuring shari'ah compliance in the industry, which is mostly conducted by interviews. In the analysis method, this study utilises the descriptive method combined with the analyticinterpretative and comparative approach. The study establishes that alongside the rapid growth and development of the Islamic banking business in both countries, the issues of shari'ah compliance arose. The issues however, have been taken up by the Malaysian and Indonesian authorities with adequate regulatory instruments in the form of the statutes (the acts of parliament), guidelines, and circular letters. It is also provided in the regulations that any product development must be approved by the shari'ah board members to ensure that they comply with shari'ah principles. The research also concludes that in both countries, the clear duties and responsibilities conferred to the shari'ah board members, good qualifications and the proper appointment procedures, supported by sufficient independence and recognition on their fatwas or decisions or resolutions, bring about more efficiency and effectiveness in the advisory or supervision roles for the sake of the implementation of shari'ah compliance. However, in terms of the enforcement of shari'ah compliance, some aspects need for enhancement. The study suggests that for Indonesia, besides repositioning the National Shari'ah Council (NSC) is needed to enable the fatwas and decisions to be binding and enforceable, the concurrent membership of the shari'ah board members is in need for reconsideration. In addition, a specific statute (the act of parliament) which covers the products and operations aspects of Islamic banking is very demanding to be enacted. In contrast, in Malaysia, the provision that the decisions and fatwas of the Shari'ah Advisory Council (SAC) is only binding over the arbitration panel, needs to be reviewed in order that those may also be binding over the court of law. Further, it is also suggested that for both countries, the introduction for the regulations of the operational aspects (shari'ah governance) of Islamic banking business need to be adopted soon to ensure the implementation in the whole aspects of the shari'ah compliance. 11